Impact of Online Self-Presentation on Fear of Missing Out and Self-Esteem Among Young Adults: The Mediating Role of Social Comparison - Amna Emaan; Aiman Siddiqui; Aneesa Abbas; Ayesha Ghafoor (Research Journal of Psychology, 2025)
The purpose of this study was to investigate the relationship between online self-presentation, Fear of missing out (FOMO) and self-esteem, considering social comparison as a mediator. A quantitative research design was employed, consisting of 200 young adults selected through convenience sampling from four institutions in Islamabad. The administered questionnaires included POSSA, FOMO, Rosenberg self-esteem scale and INCOM. Pearson’s correlation, linear regression, mediation analysis, independent samples t-test, ANOVA was used to analyze the effects of online self-presentation on FOMO, self-esteem, and social comparison, as well as influence of demographic factors involving gender, educational level, and institutions. Results indicates a significant positive relationship between online self-presentation, FOMO, and social comparison as a mediator. While, online self-presentation had a moderate positive correlation with self-esteem. The study highlights the need for social media literacy, developing interventions for healthier online behaviors, addressing online social comparison tendencies, guidance for policy makers, mental health interventions, and educational initiatives to address these issues.